(untitled) (Revista Contexto & Educação, 2026)
This article presents a methodological framework for designing intersectoral public policies in territories affected by multiple socio-environmental vulnerabilities, based on the experience of the CCAIC model (Childcare and Childhood Assistance Center) implemented in Duque de Caxias (RJ), Brazil. The research adopts a qualitative, dialectical, and interdisciplinary approach grounded in a single case study and the application of Structured Qualitative Content Analysis. Sixteen methodological guidelines were identified, anchored in the analytical categories of socio-environmental vulnerability, social inclusion, public policy, and environmental justice, and connected through intersectorality as a strategic management axis. The study’s originality lies in its empirical and theoretical translation of localized public policy practices, offering replicable guidelines for contexts with similar challenges. These directions serve as tools for planning, implementing, and evaluating policies aimed at overcoming the structural inequalities that impact childhood in Brazil’s urban peripheries.